Pengelolaan Limbah Rumah Tangga Untuk Pupuk Organik Cair Urban Farming Dalam Mencerdaskan Keterampilan Masyarakat - Rovila El Maghviroh; Nur Maf’ulla, Putri; Raihan Ahlul Firdaus; Choirunnisa’ Ainur Rohmah; Muhammad Harun Ar Rosyid; Fauzia Rahma Syaharani; Daffa Rizkidhiya Hanif; M. Ravvi Dinil Adhim; Fatchur Rohman; Azzakiyatul Amaliyah; Gadis Triyani Rasyiida; Sheryl Chintya Lena (Fakultas Teknik, Universitas PGRI Banyuwangi, 2025)
This study focuses on the innovation of converting abandoned land into organic waste disposal sites (OPC) as an eco-friendly solution to combat environmental degradation and promote sustainable urban agriculture in Simoketawang. The study found that most abandoned land is poorly managed, resulting in negative environmental impacts. The study conducted workshops with Family Welfare Movement (PKK) stakeholders, including planning, material procurement, and practical implementation of the POC. The process involved re-enriching organic waste with fresh water and air, resulting in significant improvements in community knowledge and skills. The research results show that the implementation of POC can significantly reduce environmental degradation by 70% and improve community welfare by 95% or 50,000 per month. The activity also highlights the importance of environmental protection, soil nutrition, and social learning in urban agriculture practices. However, the community service also highlights the need for ongoing training, which requires collaboration with local governments to implement the program. This activity contributes significantly to assessing community skills and transforming abandoned land into a model for sustainable urban agriculture.